THE PERFORMANCE PARADOX: WHEN SUCCESS METRICS HIDE THE TRUTH ABOUT EMPLOYEE ENGAGEMENT IN REGIONAL PLANNING AGENCIES - Munawaroh Munawaroh; Sukma Pratama; Yayu Humairoh; Riski Wulandari (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This phenomenological study explores employee engagement dynamics and organizational performance at the Regional Development Planning, Research, and Innovation Agency (BAPPERIDA) of Cilegon City. Data were collected through in-depth interviews with 12 informants, participatory observation, and document analysis. Thematic analysis revealed a performance paradox: despite satisfactory quantitative achievements (78.70% financial realization; 81.71% program indicators), employee engagement demonstrates severe hierarchical stratification. Officials and planners exhibited high vigor, dedication, and absorption, while administrative staff showed low engagement with limited performance understanding (83% did not comprehend SAKIP). Three factors enhanced engagement: holistic organizational support, participative leadership, and inclusive performance communication. Qualitative assessment revealed planning process deficiencies, weak cross-agency integration, and strategic misalignment. Findings indicate employee engagement mediates between formal performance systems and substantive outcomes. Implications include democratizing performance literacy and creating inclusive participation mechanisms across all hierarchical levels.